Insights into Intrinsic Defects and the Incorporation of Na and K in the Cu2ZnSnSe4 Thin-Film Solar Cell Material from Hybrid-Functional Calculations - Ghorbani, Elaheh; Kiss, Janos; Mirhosseini, Hossein; Schmidt, Markus; Windeln, Johannes; Kühne, Thomas D.; Felser, Claudia (Journal of Physical Chemistry C, 2016)
We have performed density functional theory calculations using the HSE06 hybrid functional to investigate the energetics, atomic, and electronic structure of intrinsic defects as well as Na and K impurities in the kesterite structure of the Cu2ZnSnSe4 (CZTSe) solar cell material. We found that both Na and K atoms prefer to be incorporated into this material as substitutional defects in the Cu sublattice. At this site highly stable (Na-Na), (K-K), and (Na-K) dumbbells can form. While Na interstitial defects are stable in CZTSe, the formation of K interstitial defects is unlikely. In general, the calculated formation energies for Na-related defects are always lower compared to their K-related counterparts. On the basis of thermodynamic charge transition level calculations, we can conclude that the external defects are harmless except NaSn and KSn. These defects induce gap states that might be detrimental for the device performance.
CRIS-Team Scopus Importer:2023-03-20